Treatment Strategy for Dyslipidemia in Cardiovascular Disease Prevention: Focus on Old and New Drugs - Donatella Zodda; Rosario Giammona; Silvia Schifilliti (Pharmacy, 2018)
Prevention and treatment of dyslipidemia should be considered as an integral part of individual cardiovascular prevention interventions, which should be addressed primarily to those at higher risk who benefit most. To date, statins remain the first-choice therapy, as they have been shown to reduce the risk of major vascular events by lowering low-density lipoprotein cholesterol (LDL-C). However, due to adherence to statin therapy or statin resistance, many patients do not reach LDL-C target levels. Ezetimibe, fibrates, and nicotinic acid represent the second-choice drugs to be used in combination with statins if lipid targets cannot be reached. In addition, anti-PCSK9 drugs (evolocumab and alirocumab) provide an effective solution for patients with familial hypercholesterolemia (FH) and statin intolerance at very high cardiovascular risk. Recently, studies demonstrated the effects of two novel lipid-lowering agents (lomitapide and mipomersen) for the management of homozygous FH by decreasing LDL-C values and reducing cardiovascular events. However, the costs for these new therapies made the cost–effectiveness debate more complicated.